Membangun Kesadaran Anti-Korupsi Melalui Media: Kajian Pemberitaan Kompas TV dalam Perspektif Pendidikan Kewarganegaraan - Adelia Yuliana; Anggita Dwi Rahayu; Laras Medina Pranitiaz; Adinda Aristias; Nasywa Awalia Putri; Tyur Reggina Dewanti; Denise Aulia Kesuma; Bryan Strom Feryan Djie; Muhamad Aria Torik Akbar; Frahnaz Amina (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2025)
This research aims to analyze the strategic role of Kompas TV in shaping public awareness of the dangers of corruption through factual, educational, and balanced reporting from the perspective of civic education. Using normative research methods, this study examines the suitability of the content and presentation of Kompas TV news with journalistic ethics standards, civic values, and anti-corruption principles as stipulated in laws and regulations. The results of the analysis show that Kompas TV consistently instils the values of honesty, transparency, and social responsibility through the coverage of corruption cases in various strategic sectors, while encouraging active public participation in social supervision and strengthening clean governance. These findings confirm that mass media reporting, especially Kompas TV, contributes significantly to building an anti-corruption culture and strengthening the character of citizens with integrity in Indonesia.